Daur Ulang Minyak Jelantah Pada Kelompok Pemuda Remaja GPDI Jemaat Ekklesia Padang Bulan, Jayapura - Herlina Menufandu; Nelly Lunga (Jurusan Biologi FMIPA Universitas Cenderawasih, 2022)
Cooking oil is not only necessary for frying but also as for flavor additive to the foods. Repeated use of cooking oil (Used Cooking Oil/ UCO) can affects its quality and caused a risk for human health. In addition, UCO could potentially be a contaminant to the environment as well. Therefore, our activity aimed to use the UCO as materials for candle making. We targeted people at the youth age as targeted community and introduce the technology to reuse UCO for candle making. Sharing information and practice was conducted to increase the enthusiasm of participants. At the end of the program, participants were able to make candles and also put some aroma therapy essence into the candle made from UCO.Â Keyword: aroma therapy; used cooking oil (UCO); candle.Â